El portafolio de productos financieros y su incidencia en los resultados de la gestión administrativa y financiera de la Cooperativa de Ahorro y Crédito Salinas Ltda, parroquia Salinas, cantón Guaranda, provincia Bolívar, año 2017 - Aguilar Aldas, Daira Noemi (2018)
The present research work is titled the Portfolio of Financial Products and its impact on the results of the Administrative and Financial Management of the Cooperativa de Ahorro y Crèdito Salinas Ltda, of the Salinas canton Guaranda parish. It is a Financial Institution whose purpose is to cover all its members through loans, savings, investments, among others, which consists of researching the portfolio of financial products and how these affect Management, Administrative and Financial. The modality applied in the present investigation is qualitative and quantitative, since in this way it is possible to expose the results found in the diagnosis of the Cooperativa de Ahorro y Crèdito Salinas Ltda, besides this, it makes use of deductive, inductive methods, analytical, descriptive, was based on field research both partners and operational staff and tools that help collect information, where you can detect the various problems experienced by the Cooperative. Thus, it is proposed to develop improvement strategies in financial products is a key opportunity for the continued growth of the institution, to attract partners, investors, and grant credits in order to satisfy partners as well as excellent attention from credit officers of the cooperative, the same that should be oriented in the continuous training of its personnel.